Pengaruh Perbandingan Ampas Kelapa (Cocos nucifera L.) dengan Jeruk Siam Kintamani (Citrus nobilis Lour.) Terhadap Karakteristik Selai - Sudrajat, Aulia Rahayu Ramadhani Satyaningtyas; Permana, I Dewa Gde Mayun; Puspawati, Ni Nyoman (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 4 (2023): Jurnal ITEPA, 2023)
This study aims to determine the effect of the ratio of coconut pulps on the characteristics of Kintamani Siamese Orange jam, as well as to determine the optimal ratio between coconut pulps and kintamani siamese orange to produce jam with desirable characteristics amd preference. This study was an experimental study using a Randomized Block Design consisting of six treatments, namely the ratio of coconut pulps and kintamani siamese orange 0: 100, 5: 95, 10: 90, 15: 85, 20: 80, and 25: 75. Each treatment was repeated 3 times, resulting in total of 18 experimental units. The obtained data were analyzed using Analysis Of Variance (ANOVA) and is there were significant effects, the Duncan Multiple Range Test (DMRT) was conducted. The results of the study showed that the ratio of coconut pulps and kintamani siamese orange in jam had a significant effect (P<0.05) on water content, viscosity, syneresis, vitamin C content, crude fiber content, total dissolved solids, and hedonic tests on color, aroma, taste and overall acceptance. The ratio of coconut pulp and Kintamani siam orange 5 : 95 has the best jam characteristics with a water content 17,24 %, total dissolved solids 51,66 %, vitamin C content 51,47 mg/g, syneresis 0%, viscosity 4.66 Pa.S, crude fiber content 1,86%, with orange color, aroma, taste, texture, and overall acceptance preferred by the panelists